Implementasi Keterampilan Dasar Komunikasi Konselor Sebaya dalam Konseling Online - Bestari, Sugestining Wisnu; Zen, Ella Faridati; Hotifah, Yuliati (Buletin Konseling Inovatif, 2025)
This study aims to understand the peer counselors’ fundamental communication skills during online counseling in Peer Counseling Corner (PCC). In this phenomenology study, we gathered data through interviews, while the data validity was confirmed through data triangulation. The obtained data were analyzed using the data horizontalization analysis. Our results indicated that the peer counselors did not implement some basic communication skills during the online counseling, such as discussion initiation, rejection (preventing and prohibiting), confrontation, and silence. Their challenges in implementing the basic communication skills include less capable of identifying the non-verbal responses from the counselees, the counselors’ decreased verbal communication skills during the counseling via chat, a time limit that does not properly function, problems in the implementation of advice, difficulties in applying the reflection of feeling, network issues, as well as the different feel and values between the offline and online counseling.